PENGARUH POLA KOMUNIKASI ORANG TUA TERHADAP PERILAKU AGRESIF ANAK USIA 5-6 TAHUN DI DESA BANGKO SEMPURNA KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Sri Dewi Pramita Sari; Daviq Chairilsyah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this research is to know the correlation between communication patterns among the elderly against aggressive behavior children aged 5-6 years in the village of Bangko Bangko Subdistrict Perfect episode of Rokan Hilir. As for the sample in this research are the parents who have children ages 5-6 years in the village of Bangko Bangko Subdistrict Perfect episode of Rokan Hilir totalling 116 heads of families (KK). Methods used i.e. survey korelasional to see the influence of communication patterns among variables variable against aggressive behavior. Data collection techniques are used namely in the form of questionnaire Likert scale. Technique of data analysis using the method of quadratic/chi-chi-square. Based on the results of the study known aggressive behavior children aged 5-6 years in the village of Bangko Bangko Subdistrict Perfect episode of Rokan Hilir is at a high category i.e. as 6 people (6.25%), categories are as many as 78 people (81.25), and the rest located in the lower categories as many as 12 people (12.5%). That is, aggressive behavior of children aged 5-6 years in the village of Bangko Bangko Subdistrict Perfect episode of Rokan Hilir views of percentage or frequency are generally classified as medium. The overall results of the study indicate that there is no communication patterns influence aggressive behavior towards children aged 5-6 years in the village of Bangko Bangko Subdistrict Perfect episode of Rokan Hilir. The results obtained from the processing of data by using the Chi Square Test. From the results of the data processing by using the Chi Square Test retrieved X 2 X 2 tables or computational < 4.623 < 9.488. If the count is smaller than X 2 X 2 table, then there is no influence between one variable against a particular variable.Key Words : Self Esteem, Interpersonal Intelligence